2015
DOI: 10.1002/ejlt.201500251
|View full text |Cite
|
Sign up to set email alerts
|

A first approach towards the development of geographical origin tracing models for North Moroccan olive oils based on triacylglycerols profiles

Abstract: The triacylglycerols composition of monovarietal Picholine Marocaine olive oils, produced in seven of the most productive areas in northern Morocco, has been established for the first time, starting a register of typicality and geographical identity of Moroccan olive oils. Two hundred seventy-nine olive samples were collected over two consecutive crop seasons (2011/2012 (n ¼ 140) and 2012/2013 (n ¼ 139)), the analysis of the triacylglycerol profiles of the obtained oils was performed using high performance liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The trilinolein content of virgin olive oil is usually less than 0.3% and it can be also used as an indication of possible adulteration of oils of foreign origin . This result confirms the findings of studies based on HPLC that used the presence of trilinolein content as a first approach toward the development of geographical origin tracing models in olive oils …”
Section: Resultssupporting
confidence: 87%
“…The trilinolein content of virgin olive oil is usually less than 0.3% and it can be also used as an indication of possible adulteration of oils of foreign origin . This result confirms the findings of studies based on HPLC that used the presence of trilinolein content as a first approach toward the development of geographical origin tracing models in olive oils …”
Section: Resultssupporting
confidence: 87%
“…[15] Having in mind the complexity of VOO matrix, the use of different metabolomic approaches giving comprehensive information about the sample under study (mainly, but not exclusively, based on MS or NMR and chemometrics) has been proposed as a way to address the problem of origin mislabeling in the olive oil sector. [21] It is worthy to mention some other interesting examples illustrating the differentiation of VOO samples according to their geographical provenance based on the determination of specific chemical classes (triacylglycerols, [22] fatty acids, [23] esterified sterols, [24] or volatile compounds [25,26] ). [17,18] Phenolic compounds profiling combined with PCA and LDA has been pointed out as a very promising approach in origin authentication studies too.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that, for most of the considered regions in the study, useful information could be extracted from TAG data for the geographical discrimination of their virgin olive oils. When considering Meknès terroir samples, rates of 93.48% in both classification and cross-validation and 82.61%, in external validation, were obtained [38].…”
Section: Chefchaouanementioning
confidence: 95%